Photolithography allows high-Q AlN microresonators for near octave-spanning frequency comb and harmonic generation - Donegan, John (My University, 2020)
Single-crystal aluminum nitride (AlN) possessing both strong Pockels and Kerr nonlinear optical effects as well as a very large band gap is a fascinating optical platform for integrated nonlinear optics. In this work, fully etched AlN-on-sapphire microresonators with a high-Q of 2.1 × 106 for the TE00 mode are firstly demonstrated with the standard photolithography technique. A near octave-spanning Kerr frequency comb ranging from 1100 to 2150 nm is generated at an on-chip power of 406 mW for the TM00 mode. Due to the high confinement, the TE10 mode also excites a Kerr comb from 1270 to 1850nm at 316 mW. In addition, frequency conversion to visible light is observed during the frequency comb generation. Our work will lead to a large-scale, low-cost, integrated nonlinear platform based on AlN.
Keywords: Single-crystal aluminum nitride (AlN); integrated nonlinear optics; frequency comb generation.